Skin surveillance intentions among family members of patients with melanoma - Coups Elliot J; Manne Sharon L; Jacobsen Paul B; Ming Michael E; Heckman Carolyn J; Lessin Stuart R (BMC, 2011)
Abstract Background First-degree relatives of individuals diagnosed with melanoma are at increased disease risk. However, many first-degree relatives do not receive a periodic total cutaneous examination from a health care provider or engage in regular skin self-examination. The goal of this study was to identify correlates of total cutaneous examination and skin self-examination intentions among first-degree relatives of melanoma patients, thus providing insight on factors that should be targeted in future intervention research. Methods The participants were 545 first-degree relatives of melanoma patients at increased disease risk due to their risk factor profile and lack of skin surveillance behaviors. Participants completed a telephone survey regarding their total cutaneous examination and skin self-examination intentions and potential correlates, including demographics, medical factors, psychological factors, knowledge, and social influence factors. Results Intentions to receive a total cutaneous examination were higher among first-degree relatives with more education, those perceiving higher benefits and lower barriers to an examination, and those reporting greater physician and family support. Intentions to receive a skin self-examination were higher among those with higher benefits and lower barriers to self-examination, and higher family support. Conclusions Interventions to promote skin surveillance behaviors among first-degree relatives of melanoma patients should highlight the benefits of early detection of melanoma, address barriers to receipt of total cutaneous examination and engagement in skin self-examination, and promote support from physicians and family members.